Perception of construction personnel towards site safety supervisor (SSS) in construction / Siti Aishah Hussin - Hussin, Siti Aishah (Faculty of Architecture, Planning and Surveying, 2013)
Safety at the construction industries always being an issue. Every year, there’s accident recorded. These include minor injury, major injury and the worst is death. Although many programs have been taken and also the monitoring from DOSH, but it seems not really effective as the accidents still occur. The latest, DOSH enforced all the construction companies with construction project that worth than RM 20 million to appoint site safety supervisor (SSS). This is to ensure the safety and health of the workers at the construction site. This dissertation is to discover the importance of SSS at the construction site in order to prevent accidents. This dissertation also done to differentiate the role and responsibilities of SSS and safety and health officer (SHO). This is because not all construction personnel know about SSS and always mistake to assume SSS as SHO. This dissertation also focused on the perception of construction personnel towards the effectiveness of SSS in construction. As already know, construction personnel are the person that works at the construction site. Construction personnel include labors, engineers, surveyors, management staff, suppliers and others. Their perception is important in order to relate the role and responsibilities of SSS with the rate of accidents at the construction site.